Music therapy : death and grief - Sekeles, Chava (Barcelona Publishers, 2007)
Seven case studies illustrating the author's clinical work with patients suffering from loss and grief, plus three chapters on the role of Israeli songs, art music, and therapist grief over patients who passed away. --From publisher's description.